Seroprevalence and risk factors associated with hepatitis C: a cross-sectional study of persons who inject drugs in Puerto Rico, 2018 - Vivian Colón-López; Paola M. Alvelo-Fernández; Nadia Centeno-Alvarado; Ivony Y. Agudelo Salas; Yadira Rolón Colón; María Pabón Martínez; Jorge L. Rodríguez-Lebrón; Juan C. Reyes-Pulliza (BMC, 2023)
Abstract Background People Who Inject Drugs (PWID) are at a higher risk of acquiring bloodborne infections. We aimed to estimate the seroprevalence of the Hepatitis C Virus (HCV) in PWID and identify correlates and risk factors using data from the Puerto Rico National HIV Behavioral Surveillance System, PWID cycle 5, conducted in 2018. Methods A total of 502 San Juan Metropolitan Statistical Area participants were recruited through the Respondent Driven Sampling method. Sociodemographic, health-related, and behavioral characteristics were assessed. Testing for HCV antibodies was completed after the face-to-face survey. Descriptive and logistic regression analyses were performed. Results Overall seroprevalence of HCV was 76.5% (95% CI: 70.8-81.4%). A significantly (p < 0.05) higher HCV seroprevalence was observed among PWID with the following characteristics: heterosexuals (78.5%), high school graduates (81.3%), tested for sexually transmitted infections (STI) in the past 12 months (86.1%), frequent speedball injection (79.4%), and knowing the HCV serostatus of the last sharing partner (95.4%). Adjusted logistic regression models showed that having completed high school and reported STI testing in the past 12 months were significantly associated with HCV infection (ORa = 2.23; 95% CI: 1.06-4.69; ORa = 2.14; 95% CI: 1.06-4.30, respectively). Conclusions We report a high seroprevalence of HCV infection in PWID. Social health disparities and potential missed opportunities validate the continuing call for local action for public health and prevention strategies.